2003
DOI: 10.1093/nar/gkg033
|View full text |Cite
|
Sign up to set email alerts
|

Database resources of the National Center for Biotechnology

Abstract: In addition to maintaining the GenBank(R) nucleic acid sequence database, the National Center for Biotechnology Information (NCBI) provides data analysis and retrieval resources for the data in GenBank and other biological data made available through NCBI's Web site. NCBI resources include Entrez, PubMed, PubMed Central (PMC), LocusLink, the NCBITaxonomy Browser, BLAST, BLAST Link (BLink), Electronic PCR (e-PCR), Open Reading Frame (ORF) Finder, References Sequence (RefSeq), UniGene, HomoloGene, ProtEST, Datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
629
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 895 publications
(648 citation statements)
references
References 27 publications
(25 reference statements)
5
629
0
3
Order By: Relevance
“…We matched all loci to the A. carolinensis genome (AnoCar2.0) using Megablast (Zhang, Schwartz, Wagner, & Miller, 2000) implemented in the database resources of the National Center for Biotechnology (NCBI; Wheeler et al., 2003). For each locus, we estimated the average number of pairwise differences between individuals within clades (π; see 3) and an estimate of genetic differentiation (Hudson, Slatkin, & Maddison, 1992) between clades.…”
Section: Methodsmentioning
confidence: 99%
“…We matched all loci to the A. carolinensis genome (AnoCar2.0) using Megablast (Zhang, Schwartz, Wagner, & Miller, 2000) implemented in the database resources of the National Center for Biotechnology (NCBI; Wheeler et al., 2003). For each locus, we estimated the average number of pairwise differences between individuals within clades (π; see 3) and an estimate of genetic differentiation (Hudson, Slatkin, & Maddison, 1992) between clades.…”
Section: Methodsmentioning
confidence: 99%
“…This demonstrated that in vivo the human gene was subject to similar control to the mouse gene. Although detailed analysis of the mouse promoter has not been reported, the mouse and human caspase 3 cDNA sequences are 83% identical (HomoloGene database 45 ) while at the protein level they are 87% identical (UniGene database 45 ). Therefore, it is likely that the gene promoters are similar in these two species also.…”
Section: Discussionmentioning
confidence: 99%
“…However in vivo, the human gene and protein appeared to be regulated as normal for their murine counterparts suggesting that caspase activity is tightly regulated under physiological conditions. This is hardly surprising considering the high degree of homology between the human and mouse caspase 3 amino-acid sequences which are 87% identical (UniGene database 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Open reading frames (ORFs) were identified using GeneWorks software (IntelliGenetics) and ORF Finder (http://www.ncbi.nlm.nih.gov/gorf/gorf.html) (Wheeler et al, 2003). The criterion for defining an ORF was a size of at least 150 nt (50 aa) with minimal overlap.…”
Section: Methodsmentioning
confidence: 99%